THE EFFECT OF CAPITAL COST AND GENERAL ALLOCATION FUND TO THE REGIONAL FINANCIAL INDEPENDENCE IN BANDUNG CITY GOVERNMENT - Hendawati, Henda; Komarasakti, Dekrita; Ansori, Surya (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
To measure the region in the field of finance performance, the level of Regional Financial Independence was used. The level of Regional Financial Independence was indicated by the size of the Local Original Income when compared with regional income derived from other sources. Several areas in West Java Province have a phenomenon where local revenues increase but local financial independence decreases. The purpose of this study is to discover the quantity of Cost of Capital, General Allocation Fund and Level of Regional Financial Independence in Bandung City during the year 2010â€“2016. In addition to that, it is also meant to comprehend the effect of Cost of Capital and General Allocation Fund to the level of Regional Financial Independence both simultaneously or partially. The research method used was multiple regression analysis by comparing the research variables namely Cost of Capital and General Allocation Fund as independent variable with the Regional Financial Independence of Bandung city area as dependent variable. The results of this study signify that Cost of Capital and General Allocation Funds have a significant effect on the city government's Regional Financial Independence. It illustrates that Cost of Capital and General Allocation Fund are able to become predictor variable to improve Regional Financial Independence. Partially the Cost of Capital has a positive influence on the level of regional autonomy while the general allocation fund has a negative effect on the level of local financial independence.Â Â